Ascetics and ambassadors of Christ the monasteries of Palestine ; 314 - 631 - Binns, John 1951- (The Oxford early Christian studies, 1994)
The monasteries of the Jerusalem desert were famous throughout the Byzantine Christian world. Yet whilst much has been written about their counterparts in Egypt and Syria, this book is the first to provide a comprehensive study of the monastic movement in Palestine during the Byzantine period, from the accession of Constantine to the fall of Jerusalem to the Persians in 614